RETURN ON ASSET, DEBT TO ASSET RATIO, QUICK RASIO AND TOTAL ASSETS TURN OVER ON STOCK PRICE IN THE CHEMICAL SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Muhammad Basri; Hade Chandra Batubara; Farisa Luvita Simatupang (Proceeding International Seminar of Islamic Studies, 2022)
The aims of this study are to: (1) To analyze and determine the effect of the variable Return on Assets to Share Prices in Chemical companies on the Indonesia Stock Exchange. (2) To analyze and determine the effect of the variable Debt To Assets Ratio to Share Prices in Chemical companies on the Indonesia Stock Exchange. (3) To analyze and determine the effect of Quick ratio to Share Prices in Chemical companies on the Indonesia Stock Exchange. (4) To analyze and determine the effect of Total Assets Turn Over to Share Prices in Chemical companies on the Indonesia Stock Exchange. (5) To analyze and determine the effect of Return On Assets, Debt To Assets Ratio, Quick Ratio and Total assets Turn Over to share prices in chemical companies on the Indonesia Stock Exchange. The population used in this study is the chemical sub-sector listed on the Indonesia Stock Exchange during 2015 to 2020, totaling 12 companies. Data collection techniques in this study using documentation techniques. The data analysis technique in this study uses the Classical Assumption Test, Multiple Linear Regression, t-test and F-test, and the Coefficient of Determination. Management of data in this study using the program Software SPSS 23. Based on the results of the study showed that Return On Assets significant positive effect on Stock price in chemical companies listed on the Indonesia Stock Exchange for the 2015 -2020 period. Debt To Assets Ratio no significant positive effect on Stock price in chemical companies listed on the Indonesia Stock Exchange for the 2015-2020 period. Quick Ratio no significant positive effect on Stock price in chemical companies listed on the Indonesia Stock Exchange for the 2015 -2020 period. Total Assets Turn Over no significant positive effect on Stock price in chemical companies listed on the Indonesia Stock Exchange for the 2015-2020 period. Return On Assets, Debt To Assets Ratio, Quick Ratio and Total Assets Turn Over jointly have a positive and significant effect on Stock price chemical companies listed on the Indonesia Stock Exchange for the 2015 -2020 period.Keywords: Return On Assets, Debt To Assets Ratio, Quick Ratio, Total Assets Turn Over and Stock Prices.